Changes of extreme precipitation in the middle and lower reaches of the Yangtze River and their correlation with atmospheric circulation - Yang, Jing; Huang, Ya; Li, Guiping; Li, Yanping (Frontiers in Earth Science, 2023)
Under the backdrop of climate change, the rising frequency and intensity of extreme precipitation events in the middle and lower Yangtze River (MLYR) region are causing serious consequences and economic losses. To assess regional risk and understand the impact of atmospheric circulation on extreme precipitation, it's crucial to analyze the spatial and temporal fluctuations of these events, focusing on the time-frequency phase relationship. Using the observed precipitation data from 1979 to 2015, nine extreme precipitation indices were calculated and a trend analysis and wavelet coherence analysis were performed to evaluate their variation. The results show that: (1) an overall increase in the frequency, intensity, and duration of precipitation in the MLYR, with significant rises in the PRCPTOT and RX1day; (2) a higher likelihood of extreme precipitation events in the southeast of the MLYR, and an uneven spatial distribution; (3) the Western Pacific Subtropical High (WPSH), the South China Sea high (SCSH), and the East Asian westerly jet (EAJ) all play a role in precipitation changes in the MLYR, with the WPSH having the most significant impact, followed by the SCSH, and the EAJ being weaker.